AN EXPLORATORY FACTOR ANALYSIS FOR DEVELOPING AND VALIDATING A SCALE OF FOREIGN WORKER'S POLICY INSTRUMENT - Nur Hidayah Zaidun; Zaheruddin Othman; Mohd Na’eim Ajis (Journal of Islamic, Social, Economics and Development, 2022)
Policy instrument is an important tool that determines the effectiveness of a policy.The capability of the policy instrument needs to be revised from time to time to ensure that theinstrument used is still relevant and appropriate. However, the current performance of foreignworkers policy has demonstrated the incapability of the policy instrument adopted. Thus, thegoal of this study is to make a revision on the questionnaire instrument developed by theresearcher in relation to the influence of the policy instrument on the performance of foreignworkers policy. The construct of this study is the policy instrument forming three dimensions(legislative, economy and communicative) that will be put to the test. All three are formed basedon the theory used which is the policy instrument theory and literature observation. A total of180 employers of foreign workers were involved as the study respondents. The study data wasanalysed descriptively. SPSS software version 22 was used to evaluate the level of reliability ofthe study instrument and the implementation of the exploratory factor analysis (EFA). Theanalysis outcome reveals that the Alpha Cronbach value obtained shows high reliability valuefor all three dimensions tested where the Alpha Cronbach values shown have respectivelyexceeded the requitement stipulated (>0.60). The analysis also establishes that the KMO(Kaiser-Meyer-Olkin) value is 0.879 which is sufficient for the inter-correlation to be carriedout. Meanwhile, the value for the Bartlett test is also significant p (0.00) < 0.05 indicating thatthe data is appropriate for the EFA implementation. However, the analysis finds that from allthe 35 items tested, there are five items that need to be removed from the instrument due to thelow factor loading (< 0.40) and the existence of cross-loading. The sum of the value for theextracted variance for the remaining 30 items is 58.27%. Thus, the overall outcome of thefinding suggests that the questionnaire instrument of the study has good validity and reliability.This instrument is also able to measure and answer the research objectives.